Algeria and the natural resource curse: oil abundance and economic growth. Issue 2 (3rd July 2017) - Chekouri, Sidi Mohammed; Chibi, Abderrahim; Benbouziane, Mohamed
Abstract : In this paper, we examine the interaction between oil exports' revenues and long-run economic growth in Algeria over the period 1979–2013. Advanced econometric procedures including the cointegration VARX (VAR with exogenous variables) model, over-identifying restrictions, bootstrapping, persistent profiles and Generalized Impulse Response Function are utilized in the empirical analysis. The results show a strong and positive association between oil revenue and long-run economic growth, but negative linkages between the volatility of oil revenues and growth in Algeria. Our impulse response analysis also provides evidence that a positive shock in oil revenues increases the level of real output, and appreciates the real exchange rate.